Ubiquitination-mediated molecular pathway alterations in human lung squamous cell carcinomas identified by quantitative ubiquitinomics - Zhan, Xianquan; Lu, Miaolong; Yang, Lamei; Yang, Jingru; Zhan, Xiaohan; Zheng, Shu; Guo, Yuna; Li, Biao; Wen, Siqi; Li, Jiajia; Li, Na (Frontiers in Endocrinology, 2022)
Abnormal ubiquitination is extensively associated with cancers. To investigate human lung cancer ubiquitination and its potential functions, quantitative ubiquitinomics was carried out between human lung squamous cell carcinoma (LSCC) and control tissues, which characterized a total of 627 ubiquitin-modified proteins (UPs) and 1209 ubiquitinated lysine sites. Those UPs were mainly involved in cell adhesion, signal transduction, and regulations of ribosome complex and proteasome complex. Thirty three UPs whose genes were also found in TCGA database were significantly related to overall survival of LSCC. Six significant networks and 234 hub molecules were obtained from the protein-protein interaction (PPI) analysis of those 627 UPs. KEGG pathway analysis of those UPs revealed 47 statistically significant pathways, and most of which were tumor-associated pathways such as mTOR, HIF-1, PI3K-Akt, and Ras signaling pathways, and intracellular protein turnover-related pathways such as ribosome complex, ubiquitin-mediated proteolysis, ER protein processing, and proteasome complex pathways. Further, the relationship analysis of ubiquitination and differentially expressed proteins shows that ubiquitination regulates two aspects of protein turnover - synthesis and degradation. This study provided the first profile of UPs and molecular networks in LSCC tissue, which is the important resource to insight into new mechanisms, and to identify new biomarkers and therapeutic targets/drugs to treat LSCC.